Pseudoprogression After Adaptive Radiation Therapy For Early-Stage Non-Small Cell Lung Cancer: Case Report - Hama, Yukihiro (International Journal of Radiology and Imaging, 2024)
Background: Differentiating local recurrence from pseudoprogression after radiotherapy for early-stage non-small cell lung cancer (NSCLC) can be challenging. Adaptive radiation therapy (ART) is an innovative radiotherapy technique that adjusts the radiation dose and treatment plan to ensure the tumor receives the optimal radiation while minimizing exposure to the surrounding healthy tissue. To our knowledge, there is no report of pseudoprogression in a patient with NSCLC who received ART. Objectives: The purpose of this article is to present the CT and 18-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) imaging findings of pseudoprogression after ART and discuss the imaging findings important for diagnosis and management. Case summaries: An 87-year-old woman with early-stage NSCLC underwent ART, receiving a total dose of 74 Gy administered in 37 fractions. The maximum standard uptake value (SUVmax) of 18F-FDG in the tumor increased from 2.5 before ART to 3.7 six months after ART on PET, suggesting local recurrence. However, the SUVmax decreased to 2.2 one year after ART, and on CT, the tumor size decreased consistently after ART. Based on serial CT and PET imaging findings, the temporal uptake of 18F-FDG at 6 months after ART was diagnosed as pseudoprogression. Conclusion: Serial CT and PET imaging findings may help differentiate local recurrence from pseudoprogression when tumor size decreases on CT but 18F-FDG uptake increases on PET. Keywords: Differential Diagnosis; Lung Neoplasms; Adaptive Radiation Therapy, Positron-emission Tomography